Simulation and design of C + L broadband communication single mode fiber - G.H. Zhang; W. Sun; F. Lei; W. Chen; Y.L. Wang; Y.T. Li; H.F. Guan; J.C. Yuan; Z. Jiang; Q.Y. Liu; Z.W. He; G.C. Tian (Results in Optics, 2023)
A novelty CL fiber which can expand L-band communication is proposed to meet the urgent demand of optical fiber transmission bandwidth for large capacity communication system. The influence of L-band attenuation on the OSNR (optical signal-to-noise ratio) of the system is analyzed and calculated; through the simulation of DWDM (dense wavelength division multiplexing) system, the requirements for FAWD (fiber attenuation warping degree) of CL fiber in 100Gbit/s rate DWDM system are obtained; and the influence of waveguide structure design on FAWD is tested. The results show that, the OSNR of L-band for will be 3 dB–3.5 dB worse than traditional C-band on 80 km span system; the FAWD@1625 nm (△α1625) and the FAWDD (fiber attenuation warping degree difference) of CL fiber are recommended to be controlled below 0.015 dB/km and 0.005 dB/km respectively to meet the link requirements in relevant standards. Additionally, it is feasible to improve the attenuation flatness of L-band by optimizing the waveguide structure design which is presented in the paper, that will provide a reference for the large-scale acquisition of novelty CL fibers in the future.